High tau levels in cerebrospinal fluid predict nursing home placement and rapid progression in Alzheimer's disease. Issue 1 (December 2016) - Degerman Gunnarsson, Malin; Ingelsson, Martin; Blennow, Kaj; Basun, Hans; Lannfelt, Lars; Kilander, Lena
Abstract Background Increased concentrations of cerebrospinal fluid (CSF) total tau (t-tau) and phosphorylated tau, as well as decreased amyloid-β 42 peptide, are biomarkers of Alzheimer's disease (AD) pathology, but few studies have shown an association with AD progression rate. We hypothesized that high CSF tau, as a marker of ongoing neurodegeneration, would predict a more aggressive course of AD, using time to nursing home placement (NHP) as the main outcome. Methods Our sample inlcuded 234 patients with mild cognitive impairment (MCI) due to AD (n = 134) or mild to moderate AD (n = 100) who underwent lumbar puncture at a memory clinic and were followed for 2–11 years (median 4.9 years). Results Individuals with CSF t-tau in the highest quartile (≥900 ng/L) had a higher ratio of NHP, both in the total cohort and in patients with MCI only (adjusted HR 2.17 [95 % CI 1.24–3.80]; HR 2.37 [95 % CI 1.10–5.09], respectively), than the lowest quartile. The association between high t-tau levels and future steep deterioration was confirmed in analyses with conversion to moderate dementia (HR 1.66; 95 % CI 1.08–2.56), rapid decline in Mini Mental State Examination score (≥4-point drop/12 months), and dying in severe dementia as outcomes. Conclusions To our knowledge, this is the first study to show that high CSF t-tau levels predict early NHP and conversion to moderate dementia in an AD cohort. Selecting patients with high CSF t-tau, indicating more aggressive neurodegeneration and steeper decline, for AD immunotherapy trials might increase the possibility of showing contrast between active treatment and placebo.